Regulation of TRPML1 channel activity and inflammatory exosome release by endogenously produced reactive oxygen species in mouse podocytes - Guangbi Li; Dandan Huang; Ningjun Li; Joseph K. Ritter; Pin-Lan Li (Redox Biology, 2021)
The nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome in podocytes has been implicated in the initiation of glomerular inflammation during hyperhomocysteinemia (hHcy). However, the mechanism by which NLRP3 inflammasome products are released from podocytes remains unknown. The present study tested whether exosome secretion from podocytes is enhanced by NADPH oxidase-produced reactive oxygen species (ROS), which may serve as a pathogenic mechanism mediating the release of inflammatory cytokines produced by the NLRP3 inflammasome in podocytes after Hcy stimulation. We first demonstrated the remarkable elevation of endogenously produced ROS in podocytes treated with Hcy compared with control podocytes, which was abolished by pre-treatment with the NADPH oxidase inhibitors, gp91 ds-tat peptide and diphenyleneiodonium (DPI). In addition, Hcy induced activation in podocytes of NLRP3 inflammasomes and the formation of multivesicular bodies (MVBs) containing inflammatory cytokines, which were prevented by treatment with gp91 ds-tat or the ROS scavenger, catalase. Given the importance of the transient receptor potential mucolipin 1 (TRPML1) channel in Ca2+-dependent lysosome trafficking and consequent lysosome-MVB interaction, we tested whether lysosomal Ca2+ release through TRPML1 channels is inhibited by endogenously produced ROS in podocytes after Hcy stimulation. By GCaMP3 Ca2+ imaging, we confirmed the inhibition of TRPML1 channel activity by Hcy which was remarkably ameliorated by catalase and gp91 ds-tat peptide. By structured illumination microscopy (SIM) and nanoparticle tracking analysis (NTA), we found that ML-SA1, a TRPML1 channel agonist, significantly enhanced lysosome-MVB interaction and reduced exosome release in podocytes, which were attenuated by Hcy. Pre-treatment of podocytes with catalase or gp91 ds-tat peptide restored ML-SA1-induced changes in lysosome-MVB interaction and exosome secretion. Moreover, we found that hydrogen peroxide (H2O2) mimicked the effect of Hcy on TRPML1 channel activity, lysosome-MVB interaction, and exosome secretion in podocytes. Based on these results, we conclude that endogenously produced ROS importantly contributes to inflammatory exosome secretion from podocytes through inhibition of TRPML1 channel activity, which may contribute to the initiation of glomerular inflammation during hHcy.